Hypoglycemic Effect of Banana Peel Extract (Musa Paradisiaca Var Kepok) in New Zealand White Rabbits with Diabetes Hyperlipidemia - Amin Samiasih; Hertanto S. W.; Edi Dharmana; Hardono Susanto (Humanistic Network for Science and Technology (HNST), 2018)
Introduction: banana peels just end up in the trash to date. It needs to be thought of waste processing into a more useful product for health. This study aims to determine the effect of peel extract Musa Paradisiaca var. kepok(MPvK) toward the blood sugar level of New Zealand White (NZW) rabbits which have diabetes hyperlipidemia. Method: 27 male New Zealand White rabbit, age 4 months, average weight 1.5-2 kg. The 104-day study was conducted at LPPT unit 4 UGM that has been standardized internationally. Results: The test results of repeated ANOVA on the blood sugar group 1 (O1) shows that at least 2 measurement times that had significantly different mean values with p-value= 0.003